A Critical Discourse Analysis on Shopee 12.12 Birthday Sale Advertisement - Kiki Feramayasari; Pangesti Wiedarti (Yayasan Visi Intan Permata, 2020)
Advertising is one of the means used to deliver and promote a product and these ads also contain elements of discourse on it. In every advertisement, impress and attract consumers are the main points such as the model, sound, picture, and verbal language that have to be used so that potential consumers will be directly connected and interest to the product being advertised by listening to, looking at, and reading. This research aims to analyze the woman’s position in Shopee 12.12 birthday sale advertisement. This research uses Sara Mills’ critical discourse analysis approach with the Feminist Stylist Approach (FSA) approach. One of the discourses which analyze about feminist sees how is the position of subject-object and the viewers on Shopee 12:12 birthday sale advertisement, then it will reveal the discourse which will be shown to the public to know the woman’s construction and to explain the pattern of woman’s construction through some scenes on Shopee 12:12 birthday sale advertisement. The focus of this research is the formulation used to analyze an advertising discourse whether it is a critical discourse or not.